2018
DOI: 10.3998/2027.42/148123
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Future national survey results on drug use, 1975-2017: Overview, key findings on adolescent drug use

Abstract: Illicit Drugs Showing Declines in Use in 2018 Relatively few drugs exhibited a significant decline in use in 2018, although the use of most drugs is well below the peak levels reached in recent years. Annual prevalence for salvia continued its gradual decline in 2018 with a significant drop of 0.2 percentage points to 0.8%. It appears that the use of this drug is close to ending. Annual tranquilizer prevalence among 12 th graders continued to fall significantly in 2018 by 0.8 percentage points to 3.9%-well bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
1,226
9
14

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,053 publications
(1,297 citation statements)
references
References 0 publications
48
1,226
9
14
Order By: Relevance
“…Heavy drinking worsens with age. The MTF survey shows that 5% of 8th graders, 11% of 10th graders, and 17% of 12th graders 13 report heavy drinking when stratified by class. A study that explored high school seniors' drinking trend from the MTF series showed that some 12th grade students reported consuming 10 to 15 alcohol drinks in rapid succession, which can dramatically increase their risk for impairment.…”
Section: Epidemiology Prevalencementioning
confidence: 98%
See 2 more Smart Citations
“…Heavy drinking worsens with age. The MTF survey shows that 5% of 8th graders, 11% of 10th graders, and 17% of 12th graders 13 report heavy drinking when stratified by class. A study that explored high school seniors' drinking trend from the MTF series showed that some 12th grade students reported consuming 10 to 15 alcohol drinks in rapid succession, which can dramatically increase their risk for impairment.…”
Section: Epidemiology Prevalencementioning
confidence: 98%
“…13 Epidemiologic studies consistently show that adolescents have a higher tendency to engage in heavy drinking or bingeing when compared with adults. 13,14 Binge drinking is defined as consuming approximately 5 or more drinks in 2 hours. Heavy drinking is 5 drinks a day for at least 5 days.…”
Section: Epidemiology Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Adolescent and young adult marijuana users have some of the highest rates and risk patterns of hazardous use, with 13.4 % of youth ages 12-17 and 38.4 % of 18-20 year olds reporting past year marijuana use in a national survey [21]. Marijuana use, particularly among adolescents and young adults, has been linked to a number of adverse consequences such as victimization, traffic accidents and fatalities, subtle impairments in cognitive functioning, and deviations in brain structure and functioning [23][24][25].…”
Section: Adolescent and Young Adult Marijuana Involvementmentioning
confidence: 99%
“…In recent years, there has been a steady, gradual increase in the proportion of youth reporting marijuana use in the USA [20], which has occurred in the context of a reduction in perceived risks of marijuana use [21] and movements to legalize recreational and medical marijuana use in the USA [22]. Adolescent and young adult marijuana users have some of the highest rates and risk patterns of hazardous use, with 13.4 % of youth ages 12-17 and 38.4 % of 18-20 year olds reporting past year marijuana use in a national survey [21].…”
Section: Adolescent and Young Adult Marijuana Involvementmentioning
confidence: 99%